Effectiveness of mosquito magnets for reducing mosquito (Diptera) populations in coastal areas of Samut Songkhram province, Thailand - Chaiphongpachara, Tanawat; Laojun, Sedthapong; Kunphichayadecha, Chaekki (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The aim of this research is to study the effectiveness of mosquito magnet (MM) for reducing mosquitoes (Diptera) populations in coastal areas. Materials and methods: The study sites are in the coastal area of Samut Songkhram province, Thailand, which is divided into two locations; one that is 2 km and another that is 4 km in distance from the sea. We used the Mosquito Magnet® Independence (MMI) trap for effective field testing in Samut Songkhram Province, Thailand. Traps were placed 100 m away from the house (one trap per location) and mosquitoes were collected at night from 6 PM to 6 AM during September and October 2017 (30 days). Results: A total of 2,561 adult mosquitoes, including Anopheles epiroticus Linton & Harbach, Culex quinquefasciatus Say, Cx. sitiens Wiedmann, and Cx. gelidus Theobald were collected by MMI. At a 2-km distance from the sea were captured more mosquitoes per night more than at a 4-km distance (63.63 ± 42.30 vs. 21.70 ± 12.42). The comparison of effectiveness of MMI in two locations of the coastal area was shown to have a statistically significant difference (p < 0.05) and analysis of the correlation between the number of mosquitoes caught in coastal areas, including at a 2- and 4-km distance from the sea, accounting for weather factors, we found that the effectiveness of MMI was not correlated with weather (p > 0.05). Conclusion: Overall, this study demonstrated that MM can be used to control mosquitoes in coastal areas with high efficiency, especially 2 km away from the sea. http://doi.org/10.5455/javar.2018.e294